Oncidium zelenkoanum (Orchidaceae), an unusual new species from Panama - Dressler, Robert L.; Pupulin, Franco (Lankesteriana: International Journal on Orchidology, 2016)
A new species, Oncidium zelenkoanum, is described from western Panama. It appears to be an isolated species, without known close relatives in Central America. The column wings have subulate, distal lobules that resemble the “awns” or “cirrhi” of some species of Odontoglossum.